A Meal Rich in Palm Oil or Butter Modifies the Sphingolipid Profile of Postprandial Triglyceride-Rich Lipoproteins From Type 2 Diabetic Patients. (14th June 2022) - Michalski, Marie-Caroline; Calzada, Catherine; Cheillan, David; Moulin, Philippe; Nazare, Julie-Anne; Pettazzoni, Magali; Boulet, Marie Michèle
Abstract: Objectives: Elevated concentrations of triglyceride-rich lipoproteins (TGRL) in the fasting and postprandial states are a risk factor for cardiovascular events in type 2 diabetes (T2D). Dyslipidemia in T2D is associated with modifications in the lipidome of plasma lipoproteins and some plasma sphingolipids (SP) have been validated as potent predictive biomarkers of cardiovascular disease occurrence. The objective of our clinical study was to determine whether sphingolipids (SP) are modified in postprandial triglyceride-rich lipoproteins (TGRL) from type 2 diabetic (T2D) patients as compared to fasting TGRL, following a saturated fatty meal. Methods: In a randomized parallel-group study, 30 T2D women ingested a breakfast including 20 g lipids from either hazelnut cocoa palm oil-rich spread (Palm Nut) or butter. TGRL were isolated by ultracentrifugation at fasting and 4 hours after the ingested meal. SP classes and SP molecular species were analyzed by tandem mass spectrometry. Results: Compared with plasma from healthy subjects, plasma from fasting T2D patients had higher ceramide (Cer, +34%) and ganglioside (GM3, +28%) concentrations, and lower concentrations of sphingosylphosphorylcholine (-66%). In postprandial TGRL compared to fasting TGRL from T2D patients, total Cer concentrations and especially C16:0, C24:1 and C24:0 molecular species, increased after the Palm Nut (+45%) or Butter (+40%) breakfast. A positive correlation was observed in the Palm Nut group between changes (D 4 h postprandial-fasting) of summed C16:0 + C22:0 + C24:1 + C24:0 Cer concentrations in TGRL, and changes in plasma TG, TGRL TG as well as TGRL C16:0 concentrations. Conclusions: The ingestion of a single fat-rich meal from a vegetable or dairy source by T2D patients led to increased concentrations of Cer in postprandial TGRL and could contribute to the increased atherogenicity of TGRL in T2D. Funding Sources: This work was supported by Inserm.